Synergetic contributions of chemical doping and epitaxial stress to polarization in ferroelectric HfO2 films. (December 2022) - Song, Tingfeng; Tan, Huan; Robert, Anne-Claire; Estandia, Saúl; Gázquez, Jaume; Sánchez, Florencio; Fina, Ignasi
Highlights: Remanent polarization of 29 μC/cm 2 is obtained in epitaxial (111) oriented doped HfO2 films. Epitaxial stress and doping effects show a positive coexisting impact on ferroelectric properties. La doped films show ferroelectricity and superior polarization than Zr doped films in a large variety of perovskite substrates. Abstract: Literature is rich on the study of different strategies to tailor ferroelectric properties of HfO2 . Among them, chemical doping is the most studied. La doped HfO2 films have attracted interest because they show very low leakage current and high endurance. On the other hand, stress controlled by substrate selection has shown to induce ferroelectric properties variations in Hf0.5 Zr0.5 O2 films. Here, we investigate stress effects in La-doped epitaxial HfO2 films. Interestingly, ferroelectricity is measured in films grown on substrates having a broad range of lattice parameter from 3.71 to 4.21 Å. While comparing the obtained results with those obtained in epitaxial Hf0.5 Zr0.5 O2, it is observed that La doped HfO2 shows always larger remanent polarization (Pr ) if the same substrate is used. Films grown on substrates with large lattice parameter (TbScO3 and GdScO3 ) show very large values of remanent polarization (29 μC/cm 2 ), but it is also noticeable that the films on substrates with small parameter (YAlO3 ) show remanent polarization above 5 μC/cm 2, whereas negligible Pr was detected in equivalent Hf0.5 Zr0.5 O2 films. Therefore, chemical doping and epitaxial stress do not compete and can be both used to synergetically tailor ferroelectric properties and eventually improve them. Graphical abstrcat: Image, graphical abstract